Natural Zeolite as Substitution Filler on the NBR/EPDM Composite: Characteristics of Swelling Resistance and Compression Set - noor maryam setyadewi; Ike Setyorini; hesty eka mayasari (Jurnal Teknologi Proses dan Inovasi Industri, 2020)
The resistance of rubber materials to solvents and compression resistance need to be studied in order to determine the proper conditions of use and storage. In this research, we will study the effect of natural zeolite as a filler substitution on the swelling characteristics and compression resistance of Nitrile Butadiene Rubber (NBR)/Ethylene Propylene Diene Rubber (EPDM) composites. The zeolite filler was varied based on the amount and treatment (5 phr and 10 phr with and without modification). The NBR/EPDM composites were made using a two-roll mill and vulcanized using a hydraulic press. Furthermore, the composites were tested for resistance to immersion (swelling) according to ISO 1817 using IRM 903, hexane, and toluene. The compression resistance testing is carried out according to ISO 815 with a compression test apparatus. From the research it is known that zeolite can be a suitable filler substitution for NBR/EPDM composites. The 10 phr modified zeolite is the most suitable filler substitution to increase immersion resistance and compression resistance for NBR/EPDM composites